Elaboração e caracterização de fermentados alcoólicos de framboesa (Rubus idaeus L.) - Silveira, Márcia Liliane Rippel (2024)
Rubus idaeus L. is a fruit species native to the Northern Hemisphere, widely cultivated and commercialized. Its fruits are rich in bioactive compounds, especially anthocyanins. However, raspberries have a short shelf life, limiting their consumption and commercialization. Thus, processing the fruits into alcoholic beverages is an alternative to utilize those that do not meet the standards for fresh consumption and to minimize losses due to their high perishability. This study aimed to characterize commercially cultivated red raspberry cultivars in Rio Grande do Sul, produce alcoholic ferments, and evaluate the possible effects of processing on the physicochemical and sensory quality of the ferment. The stability of the beverage during storage was also evaluated, monitoring the evolution of its characteristics over time. The study also sought to identify the anthocyanin profile in the fruits and alcoholic ferments. The experiment was conducted with the Autumn Bliss and Heritage cultivars over three production cycles (2013/2014, 2014/2015, and 2015/2016). The ferment was produced through the alcoholic fermentation of fruits under different experimental conditions involving the addition of sucrose and acidulant. Analyses included physicochemical properties, bioactive compound content, antioxidant activity, and sensory characteristics. Chromatographic analyses were performed for the quantitative and qualitative evaluation of the anthocyanin profile. The quality and chemical composition of the fruits were affected by both the cultivar and the production cycle. The processing of raspberries into alcoholic ferment resulted in significant changes in the chemical composition of the beverages, with a highlight on the reduction of anthocyanin content. The addition of sugar increased the alcoholic content of the beverage, while the acidulant reduced the pH and acidity of the beverages. The anthocyanin levels of the ferments decreased during the 180 days of storage, and the addition of acidulant accelerated this process, leading to the loss of the original color of the raspberry ferment, compromising the quality and stability of the product. The reduction of anthocyanins showed that raspberry ferments cannot be stored for more than 60 days. All identified anthocyanins were quantified individually. The total anthocyanin content and the individual concentrations of the compounds varied according to the cultivar and ferment treatment, but the composition of the anthocyanins proved to be independent of the analyzed variables. The ferment presented a greater qualitative complexity of anthocyanins compared to the fruits, regardless of the cultivar and treatment. The Heritage cultivar presented the highest total anthocyanin contents, both in the fruit and in the ferment. Cyanidin-3-5-diglucoside and cyanidin-3-O-sophoroside were the main anthocyanins found in the fruits and ferment of the Heritage and Autumn Bliss cultivars, respectively. The study contributes to the knowledge about raspberry processing and the production of alcoholic beverages from this fruit. The results obtained can be used to optimize the production process and develop products with higher quality and stability.